Diurnal variation of serum phosphorus concentrations in intact male adult domestic cats - Chih‐Fan Chiang; Raphael Vanderstichel; Jonathan Stockman; Jennifer A. Larsen; Andrea J. Fascetti (Journal of Veterinary Internal Medicine)
Abstract Background Monitoring serum phosphorus concentrations is crucial in the management of chronic kidney disease in cats. The diurnal variation of serum phosphorus concentration may affect clinical assessment. Hypothesis/Objectives Characterize the diurnal variation of serum phosphorus concentration in cats and determine the associations between changes in serum phosphorus concentration and several metabolites of phosphorus metabolism. Animals Six apparently healthy, intact male, specific‐pathogen‐free cats were housed in a photoperiod, humidity, and temperature‐controlled facility. Methods Blood sampling was performed hourly for 24 hours to obtain the serum concentrations of phosphorus, ionized calcium, parathyroid hormone, and calcidiol. Results were analyzed using linear mixed‐effect models to determine the significance of diurnal variation and associations between serum phosphorus concentrations and other metabolites over time. Results Diurnal variation in serum phosphorus concentration was noted with an apex around 11:00 followed by gradually declining concentrations to reach the nadir around 23:00. The serum phosphorus concentration again increased through the early morning on the next day. An approximately 25% difference in serum phosphorus concentration at the apex and the nadir was documented. A non‐linear relationship between the serum concentrations of phosphorus and ionized calcium over time was identified. Conclusions and Clinical Importance Diurnal variations of serum phosphorus concentration and associations between the trending of serum phosphorus and ionized calcium concentrations were evident in a group of clinically healthy adult cats housed in a controlled environment. These findings can help in the interpretation of clinical and research data regarding calcium and phosphorus metabolism and kidney health in cats.